Freshwater Algae (Excluding Diatoms and Red Algae) from Hasina Wetland, Sundar Haraicha, Morang, Nepal - Rai, Dilli Ram; Rai, Shiva Kumar (Himalayan Journal of Science and Technology, 2018)
This paper described 44 freshwater algae (except diatoms and red algae) belonging to classes' cyanophyceae, chlorophyceae, charophyceae and euglenophyceae from Hasina wetland and its surrounding area, Sundar- Haraicha, Morang, Nepal. Samples were collected from Budhi Khola, Khayer Khola and ponds and marshy land in Hasina wetland. In total, the largest family was chlorophyceae represented by 30 taxa and the largest genus was Cosmarium represented by 6 taxa. The study showed that this area is rich in algal diversity.